Evaluasi Pelaksanaan Pembelajaran Fiqih Di MDA PERTI Kenagarian Baruh Gunung - Vera Dika Andini (Journal of Information System and Education Development, 2026)
The paper aims to describe and evaluate the effectiveness of fiqh learning in MDA PERTI kenagarian Baruh Gunung in developing fiqh learning, which is one of the obligatory subjects of prayer, learning that contains worship that will be done by students in their daily lives. It is expected that students can understand with the learning provided so that it is correct in its implementation. The type of research carried out was an evaluation with the CIPP (context, input, process, and product) of stuffebeans. Research results found, first, the learning context that is in accordance with the prevailing vision and mission learning produces capable students. And professional educators with their knowledge; third, the quality of the fiqih education process in the understanding of students is still low because of the lack of educator attention to studentss being able to practice in daily life. Fourth, the impact of fiqh learning input quality in understanding the material and its implementation is still low